PENGARUH SOCIAL MEDIA MARKETING DAN HARGA TERHADAP MINAT BELI KONSUMEN - Khalid, Idham; Romadhoni, Buyung; Bangsawan, Gema (Jurnal Metaverse ADPERTISI, 2025)
The purpose of this study is to examine the influence of social media marketing and price on buying interest. The method used in this study is by using the survey method, where the researcher distributes questionnaires to collect data on the approach used in this study, namely the quantitative approach. The population in this study is 50 consumers who make purchases at MSMEs around the Sheikh Yusuf Gowa field. The sample size should be 10 times larger than the number of research variables, so in this study the number of samples was 50 respondents. The analysis method used is a multiple linear regression model. The results of the study found that social media marketing and prices have a positive impact on MSME actors around the Sheikh Yusuf Gowa field. With the increasing use of the internet, it is one of the opportunities for business actors to increase buying interest which has an impact on the sales of their products. Social media helps business actors in reducing promotional costs and is effective and efficient in making sales to customers. And Price has an important function in the marketing process. If the price given is too expensive, the product will not be able to reach the market price.